The Effect of Managerial Supervision and Work Motivation on Improving Principal's Performance - Susmadiana, Susmadiana; Lian, Bukman; Puspita, Yenny (Yayasan Sembilan Pemuda Indonesia, 2021)
This study focuses on the problem of the Effect of Managerial Supervision and Work Motivation on the Performance Improvement of the Principal of SMA Ogan Komering Ulu Regency. This research used questionnaire and documentation, and it is concluded that managerial supervision has a significant positive effect on employee performance. Managerial supervision has a value that is greater than the coefficient of work motivation variable. This indicates that the influence of managerial supervision variables tends to be greater in influencing employee performance than the work motivation variable, and the work motivation variable also has a positive influence on employee performance. The results of the simple regression analysis show that the t-test results are also statistically significant. It can be seen that there is a significant effect of managerial supervision and employee motivation on employee performance variables. The significant effect of this hypothesis can be seen through the F test. If F-count is greater than F-table, the independent variables have a significant effect on the dependent variable.